Effect of novel swirl distributor plate on hydrodynamics of fluidized bed gasifier - Afrooz, I.E. (Materials and Energy Research Center, 2019)
The main advantage of a fluidized bed is its capability in excellent gas-fuel mixing. However, due to the lacks of gas radial momentum, its lateral mixing of gas-solid is not adequate. Therefore, this research is focused on fluidized bed hydrodynamics enhancement using the modified gas distributor plate design. For getting an optimum fluidized bed hydrodynamics prediction, three different classical ANSYS Fluent drag models, namely Wen-Yu, Syamlal O'Brien, and Gidaspow are examined first. Afterward, a novel distributor plate called swirl distributor plate (SDP) is proposed in order to enhance the gas-fuel mixing in vertical and radial directions. In terms of simulation approach, results were presented and compared with the experimental data. It has been observed that better hydrodynamics prediction is achieved by Syamlal O'Brien drag model. The effect of SDP on gas-solid mixing was then studied numerically and compared with conventional distributor plate (CDP). Compared with CDP, better gas-solid mixing was found while the SDP was used. As a final point, gasification test was conducted in a lab scale system in order to study and compare the composition of produced syngas using both distributor plates. Based on the gasification results, SDP leads to promotion of Hydrogen and Carbon monoxide by 34.85 and 65.92 percent, respectively. Â© 2019 Materials and Energy Research Center. All rights reserved.